Pengaruh Covid-19 terhadap Pertumbuhan Fintech Pinjaman di Indonesia - Louise Louise; Yanuar Yanuar (Universitas Tarumanagara, 2022)
COVID-19 pandemic affects every economic aspect globally, including the fintech P2P lending industry in Indonesia. Indonesia’s fast P2P lending fintech growth faces challenges during the COVID-19 pandemic. This study aims to detect whether there are significant differences in Indonesia’s fintech P2P lending growth before and during the COVID-19 pandemic, especially on these 5 variables: numbers of new customers, new investors, and amount of loan disbursement, TKB90 percentage, and amount of outstanding loan. Data analysis is done using paired T-test and Wilcoxon Signed Rank Test. This study concludes that there are significant differences between new borrower and the amount of loan disbursement before and during the COVID-19 pandemic, while there are no significant differences between new investors, TKB90 percentage, and amount of outstanding loans before and during the COVID-19 pandemic. Pandemi COVID-19 berdampak pada seluruh aspek perekonomian di dunia termasuk fintech pinjaman di Indonesia. Pertumbuhan fintech pinjaman di Indonesia yang begitu pesat dalam beberapa tahun ini kini memasuki tantangan baru di era pandemi COVID-19. Penelitian ini bertujuan untuk melihat apakah terdapat perbedaan signifikan pada pertumbuhan fintech pinjaman di Indonesia sebelum dan selama pandemi melalui lima variabel jumlah peminjam baru, pendana baru, penyaluran pinjaman, angka TKB90, dan jumlah pinjaman wanprestasi fintech pinjaman di seluruh Indonesia yang terdaftar dan memiliki izin OJK. Analisis data dilakukan menggunakan metode uji T dua sampel dependen dan uji Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan pada variabel jumlah peminjam baru dan penyaluran pinjaman sebelum dan selama pandemi COVID-19, dan tidak terdapat perbedaan signifikan pada variabel jumlah pendana baru, angka TKB90, dan jumlah pinjaman wanprestasi sebelum dan selama pandemi COVID-19.